2013
DOI: 10.18060/5227
|View full text |Cite
|
Sign up to set email alerts
|

The Disproportionality of HIV Transmission Among Black Men Who Have Sex with Men (BMSM): Recommendations for an Effective Prevention Model

Abstract: The Black community shoulders the heaviest HIV/AIDS burden of any racial or ethnic group in the United States, with Black men who have sex with men being the most impacted subpopulation (CDC, 2011). Health determinants (i.e., behavior, social environment, physical environment, and healthcare) of Black men who have sex with men are examined for consideration in the creation of innovative HIV prevention programs specific to the community. The only two intervention strategies targeting this population approved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The ability of practitioners to facilitate actions that take into account these challenges and are congruent with BYMSM’s values is necessary. This is consistent with previous research that highlights the need for a community-participatory action research approach for working with this community (Castillo et al, 2012; Kubicek et al, 2013 (a); Young & McLeod, 2013). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ability of practitioners to facilitate actions that take into account these challenges and are congruent with BYMSM’s values is necessary. This is consistent with previous research that highlights the need for a community-participatory action research approach for working with this community (Castillo et al, 2012; Kubicek et al, 2013 (a); Young & McLeod, 2013). …”
Section: Discussionsupporting
confidence: 92%
“…Hurt and colleagues (2012) demonstrated a dramatic increased risk of acquiring HIV once BYMSM entered an expansive sexual network made up of young MSM of color, suggesting the risk environment of these networks contributes to the ongoing epidemic among BYMSM. This is significant because researchers have highlighted the closed nature of these BYMSM’s sexual networks may be a result of discrimination or exclusion, which can increase the community’s HIV viral load (Young & McLeod, 2013). This also suggests that for many BYMSM their sexual networks may also overlap with their social networks.…”
mentioning
confidence: 99%
“…While there have been a number of clinical trials (e.g., Grant et al, 2010) that have demonstrated that PrEP—specifically, tenofovir disoproxil fumarate/emtricitabine, or Truvada ® —is an efficacious HIV prevention option for MSM, it is concerning that there remains a limited understanding of PrEP awareness and uptake among BMSM. For example, PrEP use among BMSM, the sociodemographic group that is most heavily impacted by the U.S. HIV epidemic, continues to lag (Eaton et al, 2015; Millett, Peterson, Wolitski, & Stall, 2006; Young & McLeod, 2013). Furthermore, trials of PrEP among MSM tend to suffer from low representation of BMSM in their samples (Perez-Figueroa, Kapadia, Barton, Eddy, & Halkitis, 2015).…”
mentioning
confidence: 99%
“…13 Consistent with epidemiologic data showing men who have sex with men (MSM) to be disproportionately affected by HIV disease, most HIV prevention research efforts in black communities have focused on MSM. [14][15][16] The paucity of HIV prevention research with self-identified black, heterosexual men (BHM) has contributed to them being somewhat "invisible" in the domestic HIV epidemic. 17,18 Furthermore, studies conducted with BHM have been largely centered in settings such as correctional institutions, 19,20 clinics, 21 or urban settings.…”
mentioning
confidence: 99%